The non-inclusive nature of 'all inclusive' economics: Paradoxes and possibilities of the resort complex - Zopiatis, Anastasios; Savva, Christos S.; Lambertides, Neophytos (My University, 2020)
The 'All Inclusive' (AI) concept has revolutionized package hospitality services and captured the attention of many industry stakeholders. Scholars have mostly investigated AI from the marketing perspective, whereas the economic ramifications of this type of product, for both hospitality operators and local communities, are still a barren landscape. Using a mixture of quantitative analysis techniques, including a two-step cluster analysis and econometric modeling, the study aims to enhance our conceptual capital pertaining to the economic impact of AI for local communities. The study focuses on overall tourists' spending, both within and outside their accommodation, with expenditure segmented into seven study-specific categories that highlight the economic specificities of AI. Findings, of interest to industry stakeholders, revealed the problematic and ambiguous status of AI provision in Cyprus, whereas actions, espousing the principles of cluster theories, that could maximize the economic contribution of AI to local economies are suggested.
Keywords: All Inclusive (AI); Tourist expenditure segmentation; Economic impact; Cyprus